2021
DOI: 10.1038/s41598-021-87193-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of coronary slow flow on left atrial structure and function

Abstract: The coronary slow flow phenomenon (CSFP) is common in coronary angiography, however its impact on left atrial (LA) function is still controversial. This study aims to evaluate the LA structure and function of patients with CSFP using two-dimensional speckle tracking echocardiography (2D-STE). Consecutive patients scheduled for coronary angiography from January 2016 to September 2017 were enrolled in this study. Patients’ demographic data, clinical histories, laboratory and angiographic findings were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…However, in another study with 1:1 patient-control matching design for age, sex, hypertension, diabetes mellitus, and the LV function by Fallah [38], the authors did not find significant differences regarding triphasic LA functions assessed through 2D-STE between the CSFP group and control group. In our study [30], we found that minimum left atrial volume index (LAVImin) increased and left atrial ejection fraction (LA-EF) decreased in the CSFP group compared with the control group, although no statistically significant differences were found in the LA size (i.e., antero-posterior diameter, lateral diameter, and LA length) and maximum left atrium volume index (LAVIm) between the two groups. Meanwhile, we found that patients with CSF have lower LA-mLGS and higher late diastolic strain rate (LA-mSRa), suggesting an impairment of left atrial reservoir function and booster function in patients with CSFP.…”
Section: Csfp and Left Atrial Functionmentioning
confidence: 53%
See 1 more Smart Citation
“…However, in another study with 1:1 patient-control matching design for age, sex, hypertension, diabetes mellitus, and the LV function by Fallah [38], the authors did not find significant differences regarding triphasic LA functions assessed through 2D-STE between the CSFP group and control group. In our study [30], we found that minimum left atrial volume index (LAVImin) increased and left atrial ejection fraction (LA-EF) decreased in the CSFP group compared with the control group, although no statistically significant differences were found in the LA size (i.e., antero-posterior diameter, lateral diameter, and LA length) and maximum left atrium volume index (LAVIm) between the two groups. Meanwhile, we found that patients with CSF have lower LA-mLGS and higher late diastolic strain rate (LA-mSRa), suggesting an impairment of left atrial reservoir function and booster function in patients with CSFP.…”
Section: Csfp and Left Atrial Functionmentioning
confidence: 53%
“…In our recent study [30], we found that the percentage of monocytes has significant difference between the CSF group and the normal control group, it was an independent risk factor for the occurrence of CSFP by regression analysis, indicating monocytes may play an important role in the development of CSFP. As we know, monocytes involve in the occurrence and development of atherosclerosis, which precipitates the progression of atherosclerotic plaques from a stable state to an unstable state [31,32].…”
Section: The Pathophysiological Mechanismmentioning
confidence: 81%
“…Three studies evaluated 2D‐STE‐derived deformation markers in patients with CSFP 31,36,42 . Two reported no difference regarding Sr between the control and CSFP groups, 31,36 while the other revealed a decrease in this marker in patients with CSFP 42 . One of the 3 studies revealed decreased Scd in patients with CSFP, 31 contrary to the findings of another one of these investigations 36 .…”
Section: Resultsmentioning
confidence: 95%
“…Three studies evaluated 2D‐STE‐derived deformation markers in patients with CSFP 31,36,42 . Two reported no difference regarding Sr between the control and CSFP groups, 31,36 while the other revealed a decrease in this marker in patients with CSFP 42 .…”
Section: Resultsmentioning
confidence: 99%
“…Coronary slow-flow phenomenon (CSFP) is an angiographic phenomenon where dye passage is slow in coronary angiography in the absence of significant arterial lesions or other causes. 1 Despite considerable number of studies published since its discovery in 1972, the etiology and pathogenesis of CSFP remains unclear. CSFP is likely to lead to angina pectoris and myocardial infarction, possibly due to the impairment of coronary endothelial function, coronary microvascular lesions, early atherosclerosis, and myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%